Analisis Penerapan Perampasan Aset Terhadap Pelaku Tindak Pidana Korupsi - Keyla; ihda; Pramushinta; Shaquela; Candra; Aufaa (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Public welfare, national growth, and significant financial losses to the state are all threatened by corrupt officials. Law No. 8/2010, Law No. 20/2001, and Law No. 31/1999 are three laws in Indonesia that regulate asset confiscation. However, in reality, these regulations do not clearly regulate all aspects related to asset confiscation. The purpose of this study is to draw conclusions regarding the effectiveness of asset confiscation policies in recovering state funds lost due to corruption in law enforcement in Indonesia and how these policies have been applied to corrupt individuals in the country's criminal justice system. This study uses normative legal methods derived from conceptual and statutory sources to draw conclusions regarding the effectiveness of asset confiscation in recovering state funds lost due to corrupt public officials. The results of this study show that asset confiscation in Indonesia is implemented through two additional criminal mechanisms and civil lawsuits. However, their implementation remains suboptimal due to the reliance on final and binding criminal decisions and the existence of specific laws. Therefore, the ratification of the asset confiscation bill is necessary to increase the effectiveness of asset recovery and strengthen the eradication of corruption.